THE ROLE OF COLLABORATIVE LEADERSHIP IN IMPROVING THE QUALITY OF HIGHER EDUCATION - Robiah; Eliagus Telaumbanua; Marzuki; Zulkipli; Fiqhi Khairil Dwiputra (Adisam Publisher, 2024)
An organization's and management's success is greatly dependent on its leadership. The force that guides an organization's members' efforts toward achieving its objectives is known as leadership. For a company to compete successfully, good leadership is said to bind, harmonize, and encourage the potential of organizational resources. Higher education organizations must have collaborative leadership to monitor societal developments constantly. Higher education institutions are required to be able to adapt to various theoretical developments and institutional management concepts that continue to develop which can impact the development of higher education organizations in an even better direction. It is imperative and necessary to have highly competitive higher education institutions. Every university aspires to have a highly competitive university, but this is a difficult goal to realize. Optimizing the leadership role is crucial to reaching this objective. The notion of collaborative leadership, including academic leadership, the connection between quality and leadership in higher education, leadership theory, quality-based leadership, leadership and change in higher education, leadership as a tool to boost competition, and factors that affect collaborative leadership are all covered at the outset of the discussion. Through a literature review, descriptive-analytic techniques were employed in this qualitative research approach.